Rancang Bangun Aplikasi Optimasi Penjadwalan Produksi Pada CV. Azaria - Abraham, Mohammad Afreda Nizar; Setyawan, Henry Bambang; Sutomo, Erwin (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
CV . Azaria is a company engaged in manufacturing , which produce furniture products. Production will be carried out if the customer has sufficient orders to be produced . Production model that is currently done is to work on orders received will first be produced in advance. Production models like this will cause problems when the number of orders a lot . This will cause the production time becomes longer , causing delays in the completion of the order.Selection of appropriate models of production in accordance with the objectives to be important . Therefore we need a media that can provide optimal production models . Because the machines are owned by the work center , then the priority rules can be applied to the production model selection.By using the model of production appropriate to the purpose or parameters to be achieved then the problem of delays can be minimized. The use of priority rules in production scheduling to optimize production activities on the CV. Azaria.